MODELING OF SIMILAR ECONOMIES - S. B. Kuznetsov (Russian Journal of Economics and Law, 2017)
Objective: to obtain dimensionless criteria - economic indices characterizing the national economy and not depending on its size.Methods: mathematical modeling, theory of dimensions, processing statistical data.Results: basing on differential equations describing the national economy with the account of economical environment resistance, two dimensionless criteria are obtained, which allow to compare economies regardless of their sizes. With the theory of dimensions we show that the obtained indices are not accidental. We demonstrate the implementation of the obtained dimensionless criteria for the analysis of behavior of certain countries’ economies.Scientific novelty: the dimensionless criteria are obtained - economic indices which allow to compare economies regardless of their sizes and to analyze the dynamic changes in the economies with time.Practical significance: the obtained results can be used for dynamic and comparative analysis of different countries’ econo-mies regardless of their sizes.